Research progress of the influence of diabetes mellitus on subgingival and salivary flora with periodontitis - LIN Renjie, DAI Anna, WANG Shuhua, DING Peihui (Editorial Office of Stomatology, 2024)
In previous studies, the two-way relationship between periodontitis and diabetes has been established. Subgingival flora and salivary flora are often used to explore the relationship between the microbiome in diabetes and periodontitis. In recent years, the development of sequencing technology has provided a broader and deeper approach to exploring the impact of diabetes on oral microbiome. This review aims to summarize the effects of diabetes on subgingival flora and salivary flora in patients with periodontitis, so as to provide reference for clinical diagnosis and treatment.